All According to God's Plan : Southern Baptist Missions and Race, 1945-1970 - Willis, Alan Scot, 1968- (Book collections on Project MUSE., 2005)
"In All According to God's Plan, author Alan Scot Willis explores the tension and gradual change the race issue brought to the church. After the Supreme Court's decision in Brown v. The Board of Education, Baptist missionaries became increasingly concerned about the hypocrisy of southerners who continued to defend segregation yet claimed to be Christians. The civil rights movement further illuminated tensions between Christian beliefs and social practice in the South. As Baptist educational institutions moved closer towards integration, southern resistance to the progressive message continued."--Jacket